The Effect of Financial Ratios and Firm Size Toward Stock Price of Consumer Goods Industry Listed in the IDX - Hanifah Fathinah; Chandra Setiawan (Nusantara Science and Technology Proceedings, 2020)
This study aims to find out the effects of financial ratios and firm size toward the stock price for the consumer goods industry both partially and simultaneously with valuation ratio as a moderating variable as well as to find out the most significant independent variable. The independent variables are proxied by PBV, EPS, DER, SIZE, NPM, and lastly ROA. PER is a proxy of the valuation ratio as a moderating variable and stock price as a dependent variable. This research implements both multiple and moderated regression analysis. The population used in this research is the consumer goods industries with seven companies fulfilling the purposive sampling criteria and using quarterly data within the years 2015 to 2019. Therefore, there are 140 data observations. The results of the research reveal that only PBV does not have a statistically significant effect on the stock price. The variation of the independent variables can explain the 64.02% variation of the stock price. PER as a moderating variable can strengthen the EPS variable to influence the stock price. Among those independent variables, EPS is the most significant variable in its effect on the stock price.